1995
DOI: 10.1182/blood.v86.7.2815.2815
|View full text |Cite
|
Sign up to set email alerts
|

Polymerase chain reaction monitoring reduces the incidence of cytomegalovirus disease and the duration and side effects of antiviral therapy after bone marrow transplantation

Abstract: Culture-based preemptive therapy with ganciclovir was shown to reduce the incidence of cytomegalovirus (CMV) disease after bone marrow transplantation (BMT). Culture techniques did not detect CMV in 12% to 13% of patients before the onset of CMV disease. In a prospective study, 71 patients either received preemptive therapy based on polymerase chain reaction (PCR) technique (37 patients) or on culture assays (34 patients). In both groups, therapy was continued until clinical signs disappeared and PCR negativit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
48
0
4

Year Published

1999
1999
2014
2014

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 418 publications
(55 citation statements)
references
References 16 publications
1
48
0
4
Order By: Relevance
“…We compared these data with those from HCT recipients who had received a similar non-myeloablative HCT conditioning regimen but had received stem cells from HLA MRD. Previous studies have shown that early CMV disease after myeloablative MRD HCT occurs in 3AE8-6% of patients who were at high risk for CMV disease (CMV seropositivity before HCT), if polymerase chain reaction (PCR) or antigenaemia-based preemptive therapy approaches were applied (Einsele et al, 1995;Boeckh et al, 1999). An 11% incidence of early CMV disease has been reported after MUD myeloablative HCT (Small et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We compared these data with those from HCT recipients who had received a similar non-myeloablative HCT conditioning regimen but had received stem cells from HLA MRD. Previous studies have shown that early CMV disease after myeloablative MRD HCT occurs in 3AE8-6% of patients who were at high risk for CMV disease (CMV seropositivity before HCT), if polymerase chain reaction (PCR) or antigenaemia-based preemptive therapy approaches were applied (Einsele et al, 1995;Boeckh et al, 1999). An 11% incidence of early CMV disease has been reported after MUD myeloablative HCT (Small et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Cytomegalovirus (CMV) infections are the most common viral infections after myeloablative allogeneic haematopoietic cell transplantation (HCT). Although the diagnosis, prophylaxis and treatment have been improved over the last decade (Einsele et al, 1995;Boeckh et al, 1996;Ljungman et al, 1996), CMV infections still contribute significantly to the morbidity and mortality of patients in the early and late post-transplant periods (Husni et al, 1998;Ljungman, 1998). Risk factors for CMV infection after HCT are a positive serostatus for CMV of the recipients before HCT, acute graft-versus-host disease (GVHD), older age and unrelated or related human leucocyte antigen (HLA)mismatched donor transplants (Einsele et al, 1995;Ljungman et al, 1998).…”
mentioning
confidence: 99%
“…HCMV-seronegative, HLA-A*0201-expressing donors of buffy coat preparations were blood donors registered at the local blood bank and had been repetitively (more than three times) confirmed to be HCMV-seronegative using an enzyme-linked immunosorbent assay (ELISA) during a period of $ 1 year. No testing by polymerase chain reaction (PCR) assay was performed owing to the fact that, even with our highly sensitive PCR assay (Einsele et al, 1995), we had never been able to detect a blood sample positive for HCMV-DNA using PCR from a donor who was repetitively tested HCMV-seronegative with a sensitive ELISA assay.…”
Section: Methodsmentioning
confidence: 99%
“…Human cytomegalovirus (HCMV) infection continues to be one of the most important and life threatening infections in patients undergoing allogeneic stem cell transplantation (SCT). This herpesvirus infection still accounts for high morbidity and mortality in this patient cohort despite the introduction of new anti-viral treatment strategies (Ljungman et al, 1992;Einsele et al, 1995;Boeckh et al, 1999). Whereas early onset HCMV disease, occurring during the first 100 d post transplant, can be significantly reduced following the introduction of pre-emptive or prophylactic anti-viral therapy for HCMV infection, HCMV disease occurring after d 100 post transplantation now represents one of the leading causes of mortality after allogeneic SCT (Boeckh et al, 1999;Einsele et al, 2000).…”
mentioning
confidence: 99%
“…Consistently identified risk factors for CMV disease include CMV seropositivity, GVHD, lymphopenia, and use of alemtuzumab [47,[72][73][74]. CMV establishes latency; thus, isolation of CMV by viral culture from peripheral sites (e.g., nasopharyngeal, urine, and stool) is poorly predictive in identifying patients who will develop subsequent invasive CMV disease, and some patients who developed disease before peripheral cultures had enough time to grow [75,76]. Although CMV pp65 antigen testing of blood resulted in more rapid identification, it was limited by the need for large blood volumes and could not be used in neutropenic patients [43].…”
Section: Avian Influenzamentioning
confidence: 99%